2020
DOI: 10.1371/journal.pone.0232853
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the impacts of litter treatments on the litter quality and broiler performance: A systematic review and meta-analysis

Abstract: The choice of the most suitable litter treatment should be based on scientific evidence. This systematic review assessed the effectiveness of litter treatments on ammonia concentration, pH, moisture and pathogenic microbiota of the litter and their effects on body weight, feed intake, feed conversion and mortality of broilers. Methods The systematic literature search was conducted using PubMed (Medline), Google Scholar, ScienceDirect and Scielo databases to retrieve articles published from January 1998 to augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Recent reviews of litter treatments showed that several litter amendments are suitable for use in poultry houses to reduce litter moisture and hence ammonia generation ( Cockerill et al., 2020 ; de Toledo et al., 2020 ).…”
Section: Methodological Approachmentioning
confidence: 99%
“…Recent reviews of litter treatments showed that several litter amendments are suitable for use in poultry houses to reduce litter moisture and hence ammonia generation ( Cockerill et al., 2020 ; de Toledo et al., 2020 ).…”
Section: Methodological Approachmentioning
confidence: 99%
“…Litter treatment amendments with acidifiers including aluminium sulphate, sodium bisulphate and ferric sulphate are being used to reduce the pH of litter material. Feed supplemented with zinc, 17 charcoal 18 and Yucca schidigera plant extract 19 can also be used to reduce NH 3 concentration in the environment. Saponins and polyphenols present in Yucca schidigera extract have urease inhibiting, antioxidant and antiviral properties 20 that may result in the reduction of NH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The pH of reused litter was higher (7.12 ± 0.26) than fresh litter (6.54 ± 0.17) ( P = 0.028), while fresh litter had higher moisture (20.83 ± 3.54 %) than reused litter (14.65± 3.51 %) ( P = 0.11). Litter moisture and pH are known factors that affect pathogen survival and microbial diversity [45, 46].…”
Section: Discussionmentioning
confidence: 99%